Diritto: storia e comparazione Nuovi propositi per un binomio antico - Somma, Alessandro (Global Perspectives on Legal History, 2018)
"Comparative law and the history of law are traditionally devoted to expanding the context of legal rules and legal institutions. Comparison involves history, as the well-known motto proclaims, but history also involves comparison. Both disciplines are in fact interested in deepening the space-time coordinates of law as a social phenomenon, which means that they take up a critical approach to their object of study. In recent years, this trait is increasingly coming into conflict with the tendency to present law as a mere technocratic instrument for organizing societies. As a result of the »end of history« discourse, the Western economic and political order has become a definitive point of reference worldwide, with law scholars charged with identifying best practices to enhance their efficiency. A group of comparative lawyers and legal historians critically discuss this assumption from a theoretical point of view as well as from the perspective of their respective fields of research. The result is a multifaceted range of ideas on the significance and possible future of two disciplines that share, in addition to their traditional approach, a crisis of identity."